Novel electrosurgical knife with adjustable sheath length for colorectal endoscopic submucosal dissection. Issue 3 (4th December 2021) - Nomura, Tatsuma; Sugimoto, Shinya; Oyamada, Jun
Abstract : Watch a video of this article.